Influence of Glycyrrhiza glabra Extract on Growth, Gene Expression of Gut Integrity, and Campylobacter jejuni Colonization in Broiler Chickens - Ibrahim, Doaa; Sewid, Alaa H.; Arisha, Ahmed H.; abd El-fattah, Amir H.; Abdelaziz, Adel M.; Al-Jabr, Omar A.; Kishawy, Asmaa T. Y. (Frontiers in Veterinary Science, 2020)
Phytogenic feed additives have been gaining a considerable interest due to their ability to improve gut health and thereby performance of broiler chickens. The impact of Glycyrrhiza glabra extract (GE; liquorice) on expression of genes coding for tight junction proteins and gut protection and Campylobacter jejuni colonization in broilers not discussed until now. So, the current study assessed the effective dose of GE for maximum growth in broiler chickens, clear-cut molecular mechanisms related to integrity and health of intestine and controlling Campylobacter jejuni colonization. Over a 35 days feeding period, total 500 Ross 308 broiler chicks were fed a control diet with or without GE (0.25, 0.5, 1, 2g/kg of diet). Birds fed GE had an improved body weight gain and feed conversion ratio. Furthermore, the highest body weight gain was observed in group received 1 g/kg of GE. The expression of genes coding for tight junction proteins (occludin and Junctional adhesion molecules; JAM) was upregulated in all groups supplemented GE. Moreover, birds fed 1 g/kg of GE exhibited the maximum genes expression occludin and JAM (0.2 and 0.3fold change, respectively). In relation to enterocytes protective genes (glucagon-like Peptide; GLP-2 and fatty acid-binding protein; FABP-6), use of GE significantly upregulated expression of GLP-2 gene with 0.8fold change in 2g/kg of GE supplemented group while the expression of FABP-6 gene was not affected by GE supplementation. After challenge with C. jejuni the expression of mucin (MUC-2) gene was upregulated and the inflammatory markers as Toll-like receptors(TLR-4) and interleukin (IL-1β) was downregulated with increasing level of supplemented GE. The mean log 10 count of C. jejuni in cecal samples after seven days post infection by culture and real time-qPCR were decreased in groups fed GE in dose dependent manner. In addition, the most reduction of C. jejuni count in cecal samples by culture and real time-qPCR was observed in group fed 2g/kg of GE (2.58 and 2.28log 10 CFU/g, respectively). Results from this study suggested that Glycyrrhiza extract (1g/kg) improved growth performance of broiler chickens, as well as influenced the maintenance of intestinal integrity and reduced C. jejuni shedding from infected birds.